Effect of Acidity, Basicity and ZrO2 Phases of Cu-Ni/ZrO2 Catalysts on the Direct Synthesis of Diethyl Carbonate from CO2 and Ethanol (2023)
Cu-Ni/ZrO2 catalysts with different Cu:Ni molar ratios were synthesized and tested in the direct synthesis of diethyl carbonate from carbon dioxide and ethanol. The effect of Cu:Ni molar ratio on the acidity and basicity of the catalysts was investigated using NH3 and CO2-TPD, respectively. Experimental results revealed that Cu:Ni-3:1/ZrO2 and Cu:Ni-2:1/ZrO2 samples exhibited the largest acidity and basicity, as well as the highest yield to diethyl carbonate. In particular, these catalysts displayed very-high selectivity (i.e., larger than 95 %) and activity (i.e., equilibrium conversions are attained). Additionally, XRD and Raman studies showed that structural and crystalline properties of ZrO2 were modified with Cu:Ni ratios of 3:1 and 2:1 (Cu:Ni-1:1/ZrO2, Cu:Ni-1:2/ZrO2) which was related to the improved catalytic activity in comparison to Cu:Ni-1:1/ZrO2, Cu:Ni-1:2/ZrO2, Cu:Ni-1:3/ZrO2 and ZrO2. © 2016 Springer Science+Business Media.